EXPERIMENTAL STUDY OF FLEXURAL CFS BEAM DOUBLE CHANNEL FACE TO FACE IN LENGTH VARIATIONS - M Mirza Abdillah Pratama, Cahyana Alvyonika (BANGUNAN, 2022)
Abstract: The application of cold formed steel material as a structural element of buildings has begun to be considered because the material is strong and light. The capacity of single-section cold formed steel can be increased by combining the sections. There is less research on cold formed steel beams than columns. Research on the failure pattern of cold formed steel with variations in length has not been done before. This study aims to obtain the value of flexural capacity, deflection at maximum load, and collapse pattern of cold formed steel beams. The research was conducted experimentally on a simple supported face to face cold formed steel beam (roll-joint) by applying a four-point bending load to obtain failure due to pure bending. The results of this study indicate, the longer the face to face cold formed steel beam, the smaller the value of the load capacity that can be held and the greater the deflection value that occurs when the maximum transverse load is the Double cold formed steel beam arranged face to face experiencing instability from the beginning of loading so that the pattern failure that occurs in the form of lateral torsional buckling. Beam instability increases with increasing beam span length. A cold formed steel beam with a span length of 700 mm has a load capacity of 6.4 kN and a deflection of 14.5 mm. The failure pattern that occurs is in the form of lateral torsional buckling with a torque value of 0.74° and a lateral deflection of 0.12 mm. Cold formed steel beams with a span length of 1300 mm are capable of withstanding a maximum load of 4, 8 kN and deflection at maximum load of 32.37 mm. The beam experienced a failure pattern in the form of lateral torsional buckling with a rotation of 1.57° and a lateral deflection of 0.74 mm. The cold formed steel beam with a length of 3900 mm has a rated load capacity of 1.7 kN and a deflection of 91.49 mm. The failure pattern that occurs when the maximum load is in the form of torsional buckling of 4.02° and lateral deflection of 2.41 mm. The load capacity of the cold formed steel beam with a span length of 4300 mm is 1.4 kN and the deflection at maximum load is 99.43 mm. The beam experienced a lateral torsional buckling failure pattern with a turning angle of 12.56° and a lateral deflection of 4.84 mm. The cold formed steel beam with a length of 3900 mm has a rated load capacity of 1.7 kN and a deflection of 91.49 mm. The failure pattern that occurs when the maximum load is in the form of torsional buckling of 4.02° and lateral deflection of 2.41 mm. The load capacity of the cold formed steel beam with a span length of 4300 mm is 1.4 kN and the deflection at maximum load is 99.43 mm. The beam experienced a lateral torsional buckling failure pattern with a turning angle of 12.56° and a lateral deflection of 4.84 mm. The cold formed steel beam with a length of 3900 mm has a rated load capacity of 1.7 kN and a deflection of 91.49 mm. The failure pattern that occurs when the maximum load is in the form of torsional buckling of 4.02° and lateral deflection of 2.41 mm. The load capacity of the cold formed steel beam with a span length of 4300 mm is 1.4 kN and the deflection at maximum load is 99.43 mm. The beam experienced a lateral torsional buckling failure pattern with a turning angle of 12.56° and a lateral deflection of 4.84 mm.Keywords: Cold Formed Steel Beam, Bending Capacity, Deflection, Collapse Pattern.